Evaluation of tomato hybrids against early blight (Alternaria solani) under open field conditions - Sunita Choudhary; Rajni Singh Sasode (Annals of Agricultural Research, 2022)
Early blight disease caused by Alternaria solani is the most catastrophic disease causing losses both at pre and post-harvest stages in tomato growing places of India. An experiment was conducted for evaluation of tomato hybrids under open field conditions against early blight at College of Agriculture Gwalior Research Field during Rabi 2020-21. Total thirteen tomato hybrids were screened, out of which minimum disease were found in Cherry Tomato (4.21 per cent ) followed by Chenaya, F1 Gold Current Cherry Tomato, Abhiraj, Tomato Oblate Yellow, Deep – S – 22, Satyam, Local Hybrid 4, Tomato S Yellow Pear, Local Hybrid-1, Local Hybrid-2 and F1 hybrid tomato Sachriya while , the maximum disease intensity was found in Selection – 22 ( 58.65 per cent ).